TLE-1-Positive Angiomatoid Fibrous Histiocytoma Mimicking Synovial Sarcoma. Issue 1 (January 2019) - Zaccarini, Daniel J.; Naous, Rana; Sheth, Yesha; El-Zammar, Ola; de la Roza, Gustavo; Curtiss, Christopher M.
Abstract : Angiomatoid fibrous histiocytoma (AFH) is a rare soft tissue tumor most commonly seen in young adults and children. We report a case with morphology and immunohistochemistry supporting the diagnosis of synovial sarcoma. On core biopsy, the tumor had spindle cell and epithelioid morphology with a myxoid background. Staining for transducin-like enhancer of split 1 and CD99 were positive; however, subsequent fluorescence in situ hybridization for SYT (SS18, nBAF chromatin remodeling complex subunit) break apart returned negative. Further study showed fluorescence in situ hybridization for EWSR1 (EWS RNA binding protein 1) gene rearrangement, supporting the diagnosis of AFH. The resected specimen showed a predominant spindle cell proliferation along with histiocytoid areas supporting a diagnosis of AFH. This case report highlights the fact that synovial sarcoma and AFH can overlap morphologically and immunohistochemically. When approaching a biopsy specimen with spindle cell morphology, and transducin-like enhancer of split 1, CD99, and epithelial membrane antigen positivity it is important to include AFH in the differential diagnosis.